Praktik Stimulasi Tumbuh Kembang pada Anak Usia Dini Melalui Metode “Sensory Play” - Wida Rahma Arwiyantasari; Nisa Ardhianingtyas; Kiky Anggun Sanjaya (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Monitoring the growth and development of a child can begin from conception and will continue until adulthood, this process is mutually continuous and continuous. The development of language skills, creativity, emotional awareness, and intelligence is an important phase in a child's growth and development and is the cornerstone of subsequent development. This study aims to evaluate the ability of early childhood to improve gross motor and fine motor development skills through sensory play activities. The method of delivering information using the media of story books (fairy tales), sensory game tools that previously the children were given directions one example of simulation, then the children were directed to do independently. the results of normative identification of children's growth and development, it can be seen that from the value (5-1) range always to never, overall participants play with the highest frequency in the range is always on the cognitive and social interaction, the second position in fine & gross motor skills, and third in terms of language development and problem solving skills. The highest score level after the game, cognitive development is very significant children are very enthusiastic to follow the game conducted in groups. This activity will be better if done on an ongoing basis because it is very beneficial for early childhood development.